2011
DOI: 10.1038/nature09669
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adult nephron progenitors capable of kidney regeneration in zebrafish

Abstract: Loss of kidney function underlies many renal diseases1. Mammals can partly repair their nephrons (the functional units of the kidney), but cannot form new ones2,3. By contrast, fish add nephrons throughout their lifespan and regenerate nephrons de novo after injury4,5, providing a model for understanding how mammalian renal regeneration may be therapeutically activated. Here we trace the source of new nephrons in the adult zebrafish to small cellular aggregates containing nephron progenitors. Transplantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
377
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(391 citation statements)
references
References 22 publications
11
377
1
2
Order By: Relevance
“…The localization of a cluster of CD133þCD24þ tubular progenitors in the distal convoluted tubule and the connecting segment is also reminiscent of recent observations performed in fish [30]. Indeed, Diep et al [30] demonstrated that renal progenitors also exist in the adult kidney of the zebrafish, where they localize at the point of connection between the tubule and the duct.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The localization of a cluster of CD133þCD24þ tubular progenitors in the distal convoluted tubule and the connecting segment is also reminiscent of recent observations performed in fish [30]. Indeed, Diep et al [30] demonstrated that renal progenitors also exist in the adult kidney of the zebrafish, where they localize at the point of connection between the tubule and the duct.…”
Section: Discussionsupporting
confidence: 52%
“…This would also explain why CD133þCD24þCD106À cells selectively localize within the proximal tubule and the distal tubule that are directly generated by elongation of the S-shaped body but not in the collecting ducts that are not derived by the metanephric mesenchyme [8]. The localization of a cluster of CD133þCD24þ tubular progenitors in the distal convoluted tubule and the connecting segment is also reminiscent of recent observations performed in fish [30]. Indeed, Diep et al [30] demonstrated that renal progenitors also exist in the adult kidney of the zebrafish, where they localize at the point of connection between the tubule and the duct.…”
Section: Discussionsupporting
confidence: 51%
“…As zebrafish age, new nephrons are continually added to the kidneys. 16,38 Persistent expression of Kim-1 in the mesonephros resulted in smaller kidneys. The smaller kidneys and reduced growth of zebrafish are reminiscent of the growth retardation associated with renal disease in children and suggests a permissive role of an increase in nephrons and kidney function for growth in size of fish.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Despite the anatomic simplicity of the zebrafish pronephros (in larvae) and mesonephros (in adult fish), zebrafish models for studying AKI, polycystic kidney disease, nephronophthisis, and a range of ciliopathies have brought important insight to pathophysiologic processes in mammals. [15][16][17] Rapid breeding and development, together with ease of genetic manipulation and optical transparency, make zebrafish an ideal model organism to develop highthroughput screening for therapeutic drug discovery.…”
mentioning
confidence: 99%
“…In the past years, particularly zebrafish has been used as a model for various human diseases ranging from cancer (Etchin et al, 2011) to neurodegenerative diseases (Paquet et al, 2010;Linder et al, 2011). Of interest, zebrafish has also turned out to be an excellent model for regeneration (Jopling et al, 2010;Kikuchi et al, 2010;Diep et al, 2011). It would be desirable to use these species in aging and longevity studies, however, their maximum lifespan of up to five years (Egami, 1971;Gerhard et al, 2002) prevents them from being used as a routine model in age research.…”
Section: Introductionmentioning
confidence: 99%